A Continuous Gradient Colloidal Glass - Schöttle, Marius; Lauster, Tobias; Römling, Lukas; Vogel, Nicolas; Retsch, Markus (Advanced Materials, 2022)
Colloidal crystals and glasses manipulate light propagation depending on their chemical composition, particle morphology, and mesoscopic structure. This light-matter interaction has been intensely investigated, but a knowledge gap remains for mesostructures comprising a continuous property gradient of the constituting particles. Here, a general synthetic approach to bottom-up fabrication of continuous size gradient colloidal ensembles is introduced. Firstly, the technique synthesizes a dispersion with a specifically designed gradual particle size distribution. Secondly, self-assembly of this dispersion yields a photonic colloidal glass with a continuous size gradient from top to bottom. Local and bulk characterization methods are used to highlight the significant potential of this mesostructure, resulting in vivid structural colors along, and superior light scattering across the gradient. The process describes a general pathway to mesoscopic gradients. It can expectedly be transferred to a variety of other particle-based systems where continuous gradients will provide novel physical insights and functionalities.
Keywords: colloidal self-assembly; gradient size distribution; light scattering; mesoscale gradient

Au Nanoparticles@Si Nanowire Oligomer Arrays for SERS: Dimers Are Best - Bartschmid, Theresa; Menath, Johannes; Römling, Lukas; Vogel, Nicolas; Atalay, Furkan; Farhadi, Amin; Bourret, Gilles R. (ACS Applied Materials and Interfaces, 2024)
We report the synthesis of vertically aligned silicon nanowire (VA-SiNW) oligomer arrays coated with Au nanoparticle (NP) monolayers via a combination of colloidal lithography, metal-assisted chemical etching, and directed NP assembly. Arrays of SiNW monomers (i.e., isolated NWs), dimers, and tetramers are synthesized, decorated with AuNPs, and tested for their performance in surface-enhanced Raman spectroscopy. The ∼20 nm AuNPs easily enter within the ca. 40 nm gaps of the SiNW oligomers, thus reaching the hot spot region. At 785 nm excitation, the AuNPs@SiNW dimer arrays provide the highest Raman signal, in agreement with electromagnetic simulations showing a high electric field enhancement at the Au/Si interface within the dimer gap region.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Au nanoparticles; colloidal lithography; dimers; metal-assisted chemical etching; SERS; silicon nanowires

Breakdown of Magic Numbers in Spherical Confinement - Wang, Junwei; Martín González, Jonathan; Römling, Lukas; Englisch, Silvan; Mbah Chrameh, Fru; Bommineni, Praveen Kumar; Spiecker, Erdmann; Engel, Michael; Vogel, Nicolas (ACS nano, 2025)
Magic numbers in finite particle systems correspond to specific system sizes that allow configurations with low free energy, often exhibiting closed surface shells to maximize the number of nearest neighbors. Since their discovery in atomic nuclei, magic numbers have been essential for understanding the number-structure-property relationships in finite clusters across different scales. However, as the system size increases, the significance of magic numbers diminishes, and the precise system size at which magic number phenomena disappear remains uncertain. In this study, we investigate colloidal clusters formed through confined self-assembly. Small magic number clusters display icosahedral symmetry with closed surface shells, corresponding to pronounced free energy minima. Our findings reveal that beyond a critical system size, closed surface shells disappear, and free energy minima become less pronounced. Instead, we observe a distinct type of colloidal cluster, termed a football cluster, which retains icosahedral symmetry but features lower-coordinated facets disconnected by terraces. A sphere packing model demonstrates that forming closed surface shells becomes impossible beyond a critical system size, explaining the breakdown of magic numbers in large confined systems.
CRIS-Team Scopus Importer:2025-03-28
Keywords: clusters; colloids; confinement; self-assembly; thermodynamics

Control of Buckling of Colloidal Supraparticles - Römling, Lukas; De Angelis, Gaia; Mauch, Annika; Amstad, Esther; Vogel, Nicolas (Small, 2025)
The properties of clusters of colloidal particles, often termed supraparticles, are determined by the arrangement of the primary particles. Therefore, controlling the structure formation process is of key importance. While buckled morphologies can result from fast drying kinetics as found in spray drying, controlling the morphology under slow drying conditions remains a challenge. The final morphology of a supraparticle formed from an emulsion droplet can be controlled by manipulating particle–surfactant interactions. Water/oil emulsions are used to template supraparticle formation. The interactions of negatively charged colloidal particles with the surfactants stabilizing the water/oil-interface are tailored via the local pH within the aqueous droplet. At low pH, protonation of the anionic headgroup of the surfactant decreases electrostatic repulsion of the particles, facilitates interfacial adsorption, and subsequently causes buckling. The local pH of the aqueous droplet phase continuously changes during the assembly process. The supraparticle formation pathway can therefore be controlled by determining the point in time at which interfacial adsorption is enabled by adjusting the initial pH. Consequently, the final supraparticle morphology can be tailored at will, from fully buckled structures, via undulated surface morphologies to spherically rough and spherically smooth supraparticles and crystalline colloidal clusters.
CRIS-Team Scopus Importer:2025-05-16
Keywords: buckling; colloids; emulsions; self-assembly; supraparticles; surfactants

Crystal Structure and Defect Analysis of Colloidal Supraparticles by Lab-Based X-ray Microscopy - Englisch, Silvan; Wang, Junwei; Römling, Lukas; Voß, Johannes; Wirth, Janis; Mbah Chrameh, Fru; Apeleo Zubiri, Benjamin; Engel, Michael; Vogel, Nicolas; Spiecker, Erdmann (Microscopy and Microanalysis, 2022)
In this study, we present a systematic analysis routine for deciphering the crystallographic and defect structure of self-assembled colloidal clusters by nano X-ray microscopy (nano-XRM). The routine uses a multi-axis tilting stage for precise orientation and imaging of colloidal clusters along low-index crystallographic projections. This enables a unique identification of the crystal structure and symmetry of colloidal clusters as well as comprehensive analysis of crystallographic defects, including stacking faults, twin boundaries and lattice dislocations. The nano-XRM investigation of the inner structure of colloidal clusters is correlated with scanning electron microscopy (SEM) of the cluster surface and optical microscopy (OM) of structural color effects. Finally, the formation mechanism of colloidal clusters and their defects is discussed with the help of event-driven molecular dynamics (MD) simulation

Quantitative Optical and Structural Comparison of 3D and (2+1)D Colloidal Photonic Crystals - Römling, Lukas; Bleyer, Gudrun; Görlitzer, Eric; Onishchukov, Georgy; Vogel, Nicolas (Langmuir, 2023)
Colloidal crystals are excellent model systems to study self-assembly and structural coloration because their periodicities coincide with the wavelength range of visible light. Different assembly methods inherently introduce characteristic defects and irregularities, even with nearly monodisperse colloidal particles. Here, we investigate how these imperfections influence the structural coloration by comparing two techniques to obtain colloidal crystals. 3D colloidal crystals produced by convective assembly are well-ordered and periodically arranged but show microscopic cracks. (2+1)D colloidal crystals fabricated by stacking individual monolayers show a decreased hexagonal order and limited crystal registration between single monolayers in the z-direction. We investigate the optical properties of both systems by comparing identical numbers of layers using correlative microspectroscopy. These measurements show that the less ordered (2+1)D colloidal crystals exhibit higher reflected light intensities. Macroscopic reflection integrating all angles shows that the reflected light intensity levels out with an increasing number of layers, whereas incoherent scattering increases. Although both types of colloidal crystal show similar angle-dependent color shifts in specular reflection, the less-ordered structure of the (2+1)D colloidal crystal scatters light within a larger angular range under diffusive illumination. Our results suggest that structural coloration is surprisingly robust toward local defects and irregularities.
CRIS-Team Scopus Importer:2023-04-14

Spectro-Spatial Unmixing in Optical Microspectroscopy for Thickness Determination of Layered Materials - Schwarz, Julian; Niebauer, Michael; Römling, Lukas; Pham, Adrian; Kolesnik-Gray, Maria; Evanschitzky, Peter; Vogel, Nicolas; Krstic, Vojislav; Rommel, Mathias; Hutzler, Andreas (Advanced Optical Materials, 2025)
Van der Waals materials and devices incorporating them exhibit highly thickness-dependent properties. The small lateral dimensions of mechanically exfoliated 2D-layered flakes, however, remarkably complicate their precise thickness determination. Quantitative analysis of reflectance measurements using optical microspectroscopy is proven to be as precise as spectroscopic ellipsometry while providing an easily adaptable and non-destructive method for thickness determination. The use of magnifying objective lenses allows obtaining the reflectance within a measurement spot of only a few microns in diameter. When the dimensions of exfoliated flakes are even smaller, however, the acquired reflectance is a superposition of those of the material of interest and the subjacent materials. To overcome this limitation, a facile approach to reduce the resolvable structure size by combining the evaluation of the reflectance measurement via transfer matrix method with spatial information extracted from optical micrographs is introduced. The efficacy when characterizing micrometer-sized flakes is exemplarily demonstrated for thickness determination of highly oriented pyrolytic graphite and a thin film of silicon dioxide. It is shown that a maximum error of less than 10% is achieved even when the flake only covers 20% of the measurement spot.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 2D materials; graphite; reflectance; thin films; transfer matrix method